Synthesis of water-soluble sensitizer and photo-physicochemical studies to demonstrate its singlet oxygen generation - Atmaca, Goknur Yasa; Celep, Kevser; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The singlet oxygen quantum yield is a valuable parameter for assessing the ability of a photosensitizer to generate radical oxygen. This value is influenced by the photo-physicochemical characteristics of the sensitizer molecule. Phthalocyanines are among these complexes and as the central metal atoms and substituent groups on the phthalocyanine ring are modified, the therapeutic effects required for photodynamic therapy (PDT) can be enhanced. For this purpose, 5-bromo-2-hydroxypyridine substituted zinc phthalocyanine and its biocompatible quaternized structure are synthesized and shown to exhibit singlet oxygen efficiency with Phi Delta values reaching 0.65 in DMSO and 0.39 in water in photochemical studies. The obtained fluorescence quantum yields (Phi F) for the compounds are 0.17 in DMSO and 0.06 in water, while the photodegradation (Phi d) values are 9.1 x 10-3 in DMSO and 5.3 x 10-3 in water. This research offers valuable insights into developing water-soluble and targeted photodynamic therapies for combating cancer using photochemical applications.
Keywords: Water-soluble; Phthalocyanine; Photosensitizer; Photodynamic Therapy; Singlet oxygen; PHOTOPHYSICOCHEMICAL PROPERTIES; GALLIUM III; PHTHALOCYANINES; CANCER; Chemistry; Crystallography